2008
DOI: 10.1007/s10661-008-0230-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of benzene and formaldehyde in a medium sized urban environment. Indoor/outdoor health risk implications on special population groups

Abstract: In the present study, the results of a measurement campaign aiming to assess cancer risk among two special groups of population: policemen and laboratory technicians exposed to the toxic substances, benzene and formaldehyde are presented. The exposure is compared to general population risk. The results show that policemen working outdoor (traffic regulation, patrol on foot or in vehicles, etc.) are exposed at a significantly higher benzene concentration (3-5 times) than the general population, while the exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 29 publications
(24 reference statements)
2
21
0
Order By: Relevance
“…Wong et al (2006) stated that 9 indoor air pollutants [i.e., airborne bacterial count (ABC), carbon monoxide (CO), carbon dioxide (CO 2 ), formaldehyde (HCHO), nitrogen dioxide (NO 2 ), ozone (O 3 ), radon (Rn), respirable suspended particulates (RSP), and volatile organic compounds (VOCs)] and 3 thermal comfort parameters [i.e., air velocity (V), relative humidity (RH), and temperature (T)] could affect people's health to a certain extent. According to studies on the measurement of indoor air quality (IAQ) that have been conducted by Kim et al (2013), Pilidis et al (2009), andWong et al (2006), this variable is critical for health and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wong et al (2006) stated that 9 indoor air pollutants [i.e., airborne bacterial count (ABC), carbon monoxide (CO), carbon dioxide (CO 2 ), formaldehyde (HCHO), nitrogen dioxide (NO 2 ), ozone (O 3 ), radon (Rn), respirable suspended particulates (RSP), and volatile organic compounds (VOCs)] and 3 thermal comfort parameters [i.e., air velocity (V), relative humidity (RH), and temperature (T)] could affect people's health to a certain extent. According to studies on the measurement of indoor air quality (IAQ) that have been conducted by Kim et al (2013), Pilidis et al (2009), andWong et al (2006), this variable is critical for health and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentrations of HCHO may also induce nausea, vomiting, cough, chest tightness, and asthma, or even pneumonia, pulmonary edema, or death when exposure to over 6.5 mg·m −3 HCHO occurs (Pilidis et al, 2009). High temperature, high humidity, negative pressure, and high loading significantly accelerate HCHO diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these characteristics it was possible to propose this new risk assessment methodology, based on Queensland University proposal and make an association between occupational exposure to formaldehyde air concentrations and health effects. Recent studies [17,18] showed EPA methodology application in occupational settings with FA exposure but, as suggested by the methodology described, making use of the TWA 8h values obtained in the situations studied. Thus, applying this equation to ours results we obtain values that are lower and equal to 9,3 x10 -3 (LCP) when, the cancer risk from formaldehyde exposure in general population is 1x10 -6 LCP, and in occupational settings, will be greater than 1x10 -4 LCP [11,19].…”
Section: Discussionmentioning
confidence: 99%
“…As just one example, using the same cancer slope factor as employed in our work, Pilidis et al [8] computed predicted numerical cancer risk values due to formaldehyde in indoor and outdoor air in urban Ioannina, a medium-sized (100 000 inhabitants) city in northwestern Greece.…”
Section: Formaldehyde From E-cigarettes-it's Not As Simple As Some Sumentioning
confidence: 99%